PENATALAKSANAAN FISIOTERAPI PADA PEMAIN FUTSAL TERHADAP PENINGKATAN KEKUATAN OTOT TUNGKAI DENGAN LATIHAN LYING LEG CURL - Asriani, Dwi Suci; Mutiara, Sherly; Zaky, Abdul (LPPM Universitas Awal Bros, 2024)
Leg muscle strength is a crucial factor in the performance of futsal players, particularly in supporting movements such as running, kicking, and rapid directional changes. One of the physiotherapy methods that can be used to enhance leg muscle strength is the Lying Leg Curl exercise, which specifically targets the hamstring muscles. This study aims to analyze the effectiveness of physiotherapy management using Lying Leg Curl exercises in improving leg muscle strength in futsal players. This study employs an experimental design with a pre-test and post-test approach in the intervention group. The research sample consists of futsal players experiencing decreased leg muscle strength, selected using purposive sampling. The intervention was conducted through Lying Leg Curl exercises over a specific period, with gradually increasing intensity. Leg muscle strength was measured using a dynamometer before and after the intervention. The results indicate a significant improvement in leg muscle strength after physiotherapy intervention with Lying Leg Curl exercises (p < 0.05). These findings suggest that this exercise is effective in enhancing leg muscle strength among futsal players. Therefore, Lying Leg Curl exercises can be recommended as part of a physiotherapy program to enhance athletic performance and prevent lower limb injuries in futsal players.